Balance of privatisation policies related to foreign direct investment in the transition countries of Central and Eastern Europe - Rojec, Matija (Papeles del Este, 2005)
Foreign privatization is a special form of acquisition in which strategic investors assume control of part or all of the equity of a State-owned company in the host country. As a result of the mass privatization taking place in the Central and Eastern European countries (CEECs), foreign privatization accounted for a substantial share of the foreign direct investment (FDI) flowing into these countries. As a general rule, early privatization policies favoured domestic investors, but as the attainment of the most profitable sales price and the implementation of business restructuring gradually took over as the chief goals of privatization, foreign investors were allowed to compete on equal terms. The privatization experience in the CEECs provides evidence of the beneficial role played by Eastern country firms in post-privatization restructuring and in their own self-promotion.